SINTESIS, KARAKTERISASI, DAN APLIKASI POLIANILIN SEBAGAI POLIMER KONDUKTIF DALAM TEKNOLOGI MODERN: A REVIEW - Rifa'i, Fitra Ahmad; Saputra, Dewa Kahfi; Apriliana, Mahatma; Abidin, Luthfa Abibah Nur; Harjono, Harjono (Tanjungpura University, 2025)
Polyaniline (PANI) is a widely studied conductive polymer known for its high electrical conductivity, environmental stability, and ease of synthesis. This review critically summarizes the chemical and electrochemical synthesis routes of PANI, along with its structural and electronic characterization using FTIR, UV